BAG5 Promotes Alpha-Synuclein Oligomer Formation and Functionally Interacts With the Autophagy Adaptor Protein p62 - Friesen, Erik L.; Zhang, Yu Tong; Earnshaw, Rebecca; De Snoo, Mitch L.; O’Hara, Darren M.; Agapova, Victoria; Chau, Hien; Ngana, Sophie; Chen, Kevin S.; Kalia, Lorraine V.; Kalia, Suneil K. (Frontiers in Cell and Developmental Biology, 2020)
Molecular chaperones are critical to maintaining intracellular proteostasis and have been shown to have a protective role against alpha-synuclein mediated toxicity. Co-chaperone proteins regulate the activity of molecular chaperones and connect the chaperone network to protein degradation and cell death pathways. Bcl-2 associated athanogene 5 (BAG5) is a co-chaperone that modulates proteostasis by inhibiting the activity of Hsp70 and several E3 ubiquitin ligases, resulting in enhanced neurodegeneration in models of Parkinson’s disease (PD). Here we identify a novel interaction between BAG5 and p62/sequestosome-1 (SQSTM1), suggesting that BAG5 may bridge the chaperone network to autophagy-mediated protein degradation. We found that BAG5 enhanced the formation of pathogenic alpha-synuclein oligomers and regulated the levels and subcellular distribution of p62. These results extend the role of BAG5 in alpha-synuclein processing and intracellular proteostasis.